Extractive metallurgy of titanium : conventional and recent advances in extraction and production of titanium metal - Fang, Zhigang Zak; Froes, Francis; Zhang, Ying (Elsevier, 2020)
Extractive Metallurgy of Titanium: Conventional and Recent Advances in Extraction and Production of Titanium Metal contains information on current and developing processes for the production of titanium. The methods for producing Ti metal are grouped into two categories, including the reduction of TiCl4 and the reduction of TiO2, with their processes classified as either electrochemical or thermochemical. Descriptions of each method or process include both the fundamental principles of the method and the engineering challenges in their practice. In addition, a review of the chemical and physical characteristics of the product produced by each method is included. Sections cover the purity of titanium metal produced based on ASTM and other industry standards, energy consumption, cost and the potential environmental impacts of the processes.